Utilization of Digital Resources for Learning by Students with Intellectual Disabilities in Southern Nigeria - Ironbar, Virginia Emmanuel; Ekwok, Lawrence Nkpang; Ekpo, Mokutima E.; Ekpang, Joseph Enyia; Ogri, Eric Ugor; Oko, Benard Atrogor; Ayiba, Ojong Rose; Onigah, Emmanuel Acha; Ngwu, Ukam Ivi; Beshel, Cecilia Akpana; Ulayi, Agnes Ingiagar; Eburu, Odey Samuel; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Aim: This study investigated the use of digital resources for learning among students with intellectual disabilities in Southern Nigeria. Method: A descriptive survey design was adopted. The study involved 530 participants, including special education teachers, school administrators, and caregivers across six states in Southern Nigeria, selected through a multi-stage sampling technique. Data were collected using a structured questionnaire (DRUSEQ) with a reliability coefficient of 0.80. Descriptive statistics and Pearson’s Product Moment Correlation were used for analysis. Results: Findings revealed moderate availability of digital tools, particularly Smart Boards and text-to-speech software, but low and inconsistent usage among students with intellectual disabilities. Infrastructural and financial constraints were key barriers, with teacher training and student motivation also playing roles. While most stakeholders valued digital tools, a notable minority expressed skepticism. A statistically significant but weak positive relationship was found between digital resource usage and educators’ perceptions of student learning outcomes. Recommendation: Greater investment is needed to provide assistive digital tools and address systemic issues such as funding, internet access, and technical support in special education settings.